Balanced Scorecard use in Passenger Transport Companies Performing at Polish Market. (2017) - Tubis, Agnieszka; Werbińska-Wojciechowska, Sylwia
Abstract: The presented paper discusses the theoretical issues concerning the development and implementation of the Balanced Scorecard. Thus, the briefly literature review in this research area is provided. Following this, on the basis of the general model, there were developed pattern cards tailored to the needs of passenger transport companies performing at Polish market. The directions for further research work are defined.